Diagnosis of bovine campylobacteriosis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Science at Massey University - Chin-Fatt, Denzil X (Massey University, 1982)
Seven virgin heifers and two bulls, five and six years old respectively, were challenged with Campylobacter fetus subsp. venerealis, isolate FD15. The challenge dose consisted of approximately 10(9) organisms per ml of phosphate buffered saline (PBS)pH7.2. Cervicovaginal mucus was collected from heifers beginning one week after exposure using the technique described by Hoerlein and Kramer. These were cultured on a solid selective medium. Of the seven heifers, two became infected as determined by consistent recovery of the organism from cervical mucus samples. Seventy-four samples from both heifers were cultured; eight samples from one heifer, DO7, were discounted on the assumption that she overcame her infection. Of the sixty-six samples, forty-eight yielded the organism on culture, giving a recovery rate of 72.4%. Preputial samples were collected from the two bulls by a pipette using the technique described by Dufty. These were cultured directly and following millipore filtration on a solid selective medium. They were also examined by immunofluorescence using a similar technique to that of Dufty and Schutte. Of the thirty-two samples examined by both methods, twenty-six (81%) were positive on immunofluorescence examination, twenty-two (69%) were positive on culture, and twenty-seven (84%) were positive to both tests. It is suggested that the techniques used for sample collection and examination by culture and immunofluorescence provide an effective method for herd diagnosis of the disease.
Keywords: Campylobacter; Diseases; Cattle